ISLAMIC CORPORATE GOVERNANCE AND ISLAMICITY PERFORMANCE INDEX ON FRAUD IN SHARIA COMMERCIAL BANKS (Al Fiddhoh: Journal of Banking, Insurance, and Finance, 2024)
This study aims to impact Islamic corporate governance and fraud in Islamic banks. The Effect of Islamic Corporate Governance on Fraud in Islamic Commercial Banks. And Effect of Islamicity Performance Index on Fraud in Islamic Commercial Banks. This study uses quantitative methods and panel data on Islamic corporate governance variables. Islamicity Performance Index, and ICG and IPI Interaction. The results of this study The effect of positive ICG on fraud Regression Test Results The ICG variable has a coefficient of 4,377,977 and a probability of 0.015, more excellent than 0.05 based on the test. The ICG variable statistically means that the higher the ICG score, the more fraud cases increase, which results in a positive IPI influence on fraud. The results of the Regression Test Variable X1 has a coefficient of 3.536459 and a probability of 0.043, which is less than 0.05, while the variable X2 has a coefficient of -6.62755 and a probability of 0.003 is less than 0.05, which means that isn't it according to theory? If ICG and IPI increase, fraud will decrease, and Interaction Results in This Research Produce a new Variable. Regression Test Results Variable X1 has a coefficient of 17.47975 and a Probability of 0.007, which is less than 0.05, and Variable X2 has a coefficient of 4.735987 and a Probability of 0.406, which is more significant than 0.05 can be interpreted in the same direction and the Interaction Between X1, X2 ICG and IPI can be said to be Perfect that ICG Initially positive, from the ICG results, IPI becomes negative. Significantly, the higher the IPI score. An increase in ICG will reduce fraud cases.